ANALISIS NILAI TAMBAH DAN STRATEGI PENGEMBANGAN INDUSTRI RUMAH TANGGA OLAHAN JAGUNG DI KABUPATEN GROBOGAN - , SHOFIA NUR AWAMI ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research aimed (1) to determine the amount of added value and the feasibility of corn processing home industry in Grobogan District, (2) to analyze the factors that influenced added value of corn processing home industry, (3) to investigate the contribution of corn processing home industry to total household income, and (4) to formulate development strategy for home industry corn processing in Grobogan District. This research covered analysis methods several including, the added value Analysis according Hayami, et all (1987), the feasibility analysis, Multiple linear regression analysis with Cobb Douglasâs product functional models function to determine the factors that affect the added value of corn processing and SWOT Analysis. The added value of processing corn into chips is Rp. 4574 per kilogram and for marning Rp. 2823 per kilogram, Value added is a gross added value to the producers since it has not reduced by laborâs wage. The monthly average total revenue for corn processing production into corn chip of Rp.5.264.225 and into marning of Rp.5.583.888 with the average profit obtained entrepreneur is Rp.732.692 and Rp. 444,230 respectively. RC ratio value of corn processing into corn chips amounted 1,18 and RC ratio value of corn processing into marning of 1,09. Furthermore, units BEP of processing corn chips amount to 29,38 kilogram and the production value BEP is Rp. 452.221. The calculations of units BEP of processing marning amount to 65,35 kilogram and production value BEP is Rp. 847.731. Added value of processed corn products in Grobogan Districtwere influenced by several factors including